1976
DOI: 10.3181/00379727-151-39244
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Erythropoietin and Prostaglandin E Production in the Dog following Renal Artery Constriction

Abstract: The precise mechanism of erythropoietin (ESF) production and release from the kidney still remains obscure although it is well known that many forms of hypoxia, e.g., anemic, hypoxic, ischemic, and histotoxic, are capable of increasing erythropoietin production by the kidney (1). Recent observations (2, 3) indicate that following renal artery constriction in the dog, there is a release of prostaglandins (PG) into the renal venous blood. We have reported recently (4-6) that both hypoxic and ischemic hypoxia are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
5
1
1
Order By: Relevance
“…We have demonstrated that Epo production in this system does not appear to be dependent upon cyclooxygenase products, such as PGE2, in contrast to the mechanism previously suggested in other systems (48)(49)(50)(51). PGE2 is not produced by either HepG2 or Hep3B cells, and Epo production is not significantly impaired when hypoxic Hep3B cells are grown in the presence of indomethacin, a potent cyclooxygenase inhibitor.…”
Section: Discussioncontrasting
confidence: 47%
“…We have demonstrated that Epo production in this system does not appear to be dependent upon cyclooxygenase products, such as PGE2, in contrast to the mechanism previously suggested in other systems (48)(49)(50)(51). PGE2 is not produced by either HepG2 or Hep3B cells, and Epo production is not significantly impaired when hypoxic Hep3B cells are grown in the presence of indomethacin, a potent cyclooxygenase inhibitor.…”
Section: Discussioncontrasting
confidence: 47%
“…Unter denjenigen biochemischen Pa rametern, die eine Hypoxiereaktion vermitteln könnten, werden die Prostaglandine als ernsthafte Kandidaten betrachtet. Dies beruht auf folgenden Erkenntnissen: 1) verschiedene Gewebe, einschliesslich der Nieren, setzen auf Hypoxie hin mehr Prostaglandine frei [47,48]; 2) die Prostaglandine können die Bildung von EPO in der Nie re [49,50] und in Zellkulturen [51] stimulieren, und 3) die Hemmung der Prostaglandinbildung hemmt die durch CL-Mangel induzierte Bildung von EPO in vivo [21,52,53].…”
Section: Zelluläre Regulation Der Epo-produktionunclassified
“…Another stimulus which leads to an increase in renin release from the kidney is renal artery constriction (Johns & Singer, 1974). This stimulus has 37 also been reported to induce an increase in the release of prostaglandin from the kidney in the dog (McGiff, Crowshaw, Terragno, Lonigro, Strand, Williamson, Lee & Ng, 1970;Gross, Mujovic, Jubiz & Fisher, 1976). Although these results suggest that the increased formation of angiotensin II within the kidney leads to the local formation of prostaglandin, other evidence indicates that the relationship between these substances is very complex, and that the kallikrein-kinin system may also be involved.…”
Section: Introductionmentioning
confidence: 97%